Transverse Momentum Dependence on Fourier Elliptic and Triangular Flow Harmonics in Mid-Central Pbpb Collisions at SNN=2.76TeV. Issue 1 (1st December 2022) - Zhang, Shi; Wang, Zimo; Li, Xinwei; Shen, Ruolin; Ouyang, Chengxuan
Abstract: We have collected particle collision data from the experiment using CMS apparatus, where we studied charged ions in the nucleus-to-nucleus collision's PbPb branch in Pb at the 2.76 TeV energy scale. So far for the present work, we report the anisotropy of the thermal observational flux in lead-lead nucleon collisions at sqrt = 2.76 TeV. We observed that the collisions produced a large ion azimuth angle ranging from − π to π radian and a pseudo-conductance ranging from -2.6 to 2.6. In this work, we report the correlation function of transverse momentum, Pt, Δη, and ΔΦ over a wide range of centroids. When the transverse momentum is about 1-2 GeV/c and Δ η is in range -1 to 1, we observe a jet peak in the η and Φ correlation plot as the centrality increases. In the case of ν 2, which is an elliptic current signal, we measured it with a 4-part correlation method in the 40-50% centrality class. Asymptotic angular correlations in the far range have been studied by Fourier decomposition on the product of anisotropies when the cross-correlation is equal to 3-3.5 GeV/c. The obtained Fourier coefficients are factorized into the singular product of -ion Φ anisotropies. The assumptions of the hydrodynamic model with the shear viscosity correlation increase accordingly.